Nonlinear dynamics of two harmonic oscillators coupled by Rayleigh type self-exciting force - Chatterjee, S.; Dey, Somnath (Nonlinear dynamics, 2013)
The present paper reports some interesting phenomena observed in the nonlinear dynamics of two self-excitedly coupled harmonic oscillators. The system under consideration consists of two mechanical oscillators coupled by the Rayleigh type self-exciting force. Both autonomous and nonautonomous cases for weakly coupled systems are analyzed. When the natural frequencies of the two oscillators are close to each other, only one mode of oscillation exists. As two modes of oscillations get locked to a single mode, the system is said to be in a mode-locked condition. Under a mode-locked condition, the oscillators can oscillate with only a single frequency. However, when two oscillators are sufficiently detuned, the mode-locking condition does not persist and two distinct modes of oscillations emerge. Under these circumstances, particularly when detuning is large, one of the oscillators, depending on the initial conditions, oscillates with much larger amplitude as compared to the other oscillator, and hence mode localization is observed. When one of the oscillators is subject to a harmonic excitation, at two different frequencies, termed here as the decoupling frequencies, the coupling between the oscillators is almost lost, resulting in almost zero response of the unexcited oscillator. Analytical and numerical results are presented to analyze the above mentioned phenomena. Some potential applications of the aforesaid phenomena are also discussed.